MANAGING THE PRODUCTIVE ZAKAT FUND: THE CASE OF BAZNAS KAPUAS - Zaki Mubarak; Hanifah Hanifah (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Islam requires rich Muslims to distribute their wealth through zakat. Therefore, zakat can be used as one of the economic policies to help regulate the turnover of wealth in a country to help solve the problem of poverty. BAZNAS is a zakat management organization formed by the Indonesian government to manage zakat funds. One of the programs of BAZNAS is productive zakat which aims to help the mustahik in the long term by providing business capital. This study aims to find out how productive zakat fund management is and the obstacles faced because there are still not many studies that discuss how productive zakat management is and the obstacles faced. This research is qualitative in collecting data using interviews with the Chairman and reporting department of BAZNAS Kapuas Regency. The results showed that the management of productive zakat funds in BAZNAS Kapuas Regency was carried out through the Kapuas creative program by distributing productive zakat funds used to help business capital. However, BAZNAS managers experience problems raising funds, which are caused by the lack of public understanding of zakat management institutions such as BAZNAS, so they tend to distribute their zakat funds directly. The results of the research are important for BAZNAS to carry out better management of zakat funds and provide an understanding of the function of BAZNAS to the community to increase the number of zakat funds that can be collected.